1996
DOI: 10.1046/j.1365-2958.1996.6491364.x
|View full text |Cite
|
Sign up to set email alerts
|

afsR is a pleiotropic but conditionally required regulatory gene for antibiotic production in Streptomyces coelicolor A3(2)

Abstract: The N-terminal region of AfsR, a putative pleiotropic regulatory protein for antibiotic production in Streptomyces coelicolor A3(2), is homologous to RedD and Actil-ORF4, pathway-specific regulatory proteins required for the production of the antibiotics undecylprodigiosin (Red) and actinorhodin (Act), respectively. The recent identification of afsS, which lies immediately 3' of afsR and which stimulates antibiotic production when cloned at high copy number, questioned whether afsR was a pleiotropic regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
197
2
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 29 publications
10
197
2
2
Order By: Relevance
“…OzmR shows significant similarity to the LysR family of regulators, such as Orf5 (accession number BAA32133; 53% identity) from Streptomyces griseus (38), whereas OzmU belongs to the SARP family of regulators, including Orf31* (accession number CAG15043; 37% identity) involved in glycopeptide teicoplanin biosynthesis in Actinoplanes teichomyceticus (39), AfsR (accession number BAA14186; 33% identity) in Streptomyces coelicolor, a pleiotropic antibiotic regulator (40), and RubS (accession number AAM97369; 30% identity) involved in rubromycin biosynthesis in Streptomyces collinus. Although OzmT resembles other Thr-tRNA synthetases, such as SCH63.25 (CAC 10316, 77/83) in S. coelicolor, its exact roles still need to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…OzmR shows significant similarity to the LysR family of regulators, such as Orf5 (accession number BAA32133; 53% identity) from Streptomyces griseus (38), whereas OzmU belongs to the SARP family of regulators, including Orf31* (accession number CAG15043; 37% identity) involved in glycopeptide teicoplanin biosynthesis in Actinoplanes teichomyceticus (39), AfsR (accession number BAA14186; 33% identity) in Streptomyces coelicolor, a pleiotropic antibiotic regulator (40), and RubS (accession number AAM97369; 30% identity) involved in rubromycin biosynthesis in Streptomyces collinus. Although OzmT resembles other Thr-tRNA synthetases, such as SCH63.25 (CAC 10316, 77/83) in S. coelicolor, its exact roles still need to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Two regulatory proteins, AcoK and AlkS, from Gram-negative organisms are involved, like MalT, in regulating catabolic functions (acetoin and alkane degradation, respectively ; Peng et al, 1997 ;Yuste et al, 1998). Several members of this protein family come from streptomycetes ; the LipR proteins are clearly involved in regulating a catabolic function, whereas others appear to be involved in regulating antibiotic synthesis, either as part of a cluster (PikD, RapH and its homologue RapHh ; Xue et al, 1998 ;Molnar et al, 1996 ;Ruan et al, 1997) or as pleiotropic regulators (AfsR ; Floriano & Bibb, 1996). Analysis of sequence relationships revealed that the Streptomyces proteins group according to function, with those that are part of antibiotic biosynthesis clusters forming one sub-group, and LipR belonging to another.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, the only available data point to a role of some of these proteins, such as GutR from Bacillus subtilis and AfsR from Streptomyces coelicolor, in transcription regulation. 57,58 The GutR protein, which is a regulator of the glucitol operon, has been shown to function in an ATP-dependent manner. 59 The AfsR protein is a global regulator of physiological and morphological differentiation in Streptomyces and is itself regulated by reversible phosphorylation catalyzed by the serine-threonine kinase AfsK.…”
Section: Other Ancient Apoptotic Proteinsmentioning
confidence: 99%